The Internationalization of Post-Secondary Education in Manitoba: A Critique of Two Government Policy Approaches, 1999 - 2021 - Browning, Kimberly; Elnagar, Abdelhady (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2022)
International education has become a policy sector of increasing importance to the Canadian province of Manitoba. Provincial governments with opposing political ideologies can impact international education policy differently. Using narratives as an analytical framework, we identify themes by examining the approaches taken to the international post-secondary education (PSE) sector in Manitoba under the last two governments that held office. The analysis reveals that while both governments’ policies are underpinned by neoliberalism reflecting the economic benefits of international student recruitment and retention, key differences are identified. While cultural diversity and global understanding, policy coordination and collaboration, associated leadership, strategy, and a regulatory framework were important components of international PSE policy, there has been a discernible shift towards an austerity agenda, free market policies, and a reconceptualization of international PSE as an immigration-focused policy. The paper concludes that the current government’s focus on labour markets and immigration when it comes to international PSE means that other aspects of internationalization are little understood and supported.